2011
DOI: 10.1177/155005941104200404
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison among Several P300 Brain-Computer Interface Speller Paradigms

Abstract: Since the brain-computer interface (BCI) speller was first proposed by Farwell and Donchin, there have been modifications in the visual aspects of P300 paradigms. Most of the changes are based on the original matrix format such as changes in the number of rows and columns, font size, flash/ blank time, and flash order. The improvement in the resulting accuracy and speed of such systems has always been the ultimate goal. In this study, we have compared several different speller paradigms including row-column, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 16 publications
0
22
0
1
Order By: Relevance
“…However, additional recording sites [9], [10], [68], designs [41], [43], [44], [69], [70] and classifiers [14], [71] have been reported to influence performances achieved with those systems. Thus different results could be obtained using different electrode sites, stimulation design and/or signal processing/classification techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, additional recording sites [9], [10], [68], designs [41], [43], [44], [69], [70] and classifiers [14], [71] have been reported to influence performances achieved with those systems. Thus different results could be obtained using different electrode sites, stimulation design and/or signal processing/classification techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Although other alternatives to the traditional row/column paradigm have been suggested [11], [41][44], we decided to use the single symbol design because it minimizes the amount of distracting stimuli with respect to the target stimulus, which for some patients was a major concern.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that the overall spelling accuracies averaged for the same set of subjects, trials, and characters for RC, SC, and two variations of RB paradigms were 85%, 72.2%, 90.6%, and 86.1%, respectively, (Fazel-Rezai et al, 2011). The RB and CB paradigms show a new direction in P300 BCI that can produce superior performance, and may generally reduce the need for the RC approach to P300 BCIs.…”
Section: Visual P300 Paradigmsmentioning
confidence: 99%
“…Unfortunately, such an action reduces the frequency of the target stimulation and, thereby, reduces the overall system speed. This tradeoff has been explored in several early BCI studies [14]. It is evident that due to the nature of P300 ERP generation, P300 amplitude can be increased by incorporating high temporal uncertainty.…”
Section: P300 Detectionmentioning
confidence: 99%
“…The list of characters used in seven regions in the first level of this modified edition is presented in Table 2. In a comparative study, it was found that the overall spelling accuracies averaged for the same set of subjects, trials, and characters for RC, SC, and two variations of RB paradigms were 85, 72.2, 86.1, and 90.6%, respectively [14,69]. It is interesting to note that other than P300 BCI, application of RB paradigm has been extended to other BCI modalities too [54,[70][71][72].…”
Section: Region-based (Rb) Paradigmmentioning
confidence: 99%